Absolute pitch and its effects in music activities: evaluation and self-perception of conservatory students - Laucirica, Ana (2023)
The systems intended to evaluate absolute pitch (AP) display a high variability regarding their configuration, which could be attributed to the complex definition of the concept. Also, studies delving into the effects that AP produces in music activities are rare, and usually with contradictory results. The current study is aimed to inquire into the AP evaluation systems and the self-perception of a group composed of 23 professional-grade music students with such profile to understand (a) the intensity of the practice of different music activities (memorization, improvisation, sight-reading, transposition, intonation, intervals identification and dictation), (b) the behavior of their musical hearing when performing them and (c) the influence that AP exerts over the performance of the aforementioned activities. In a previous study students undertook an AP test to classify them (partial, shifted and partial, or Quasi-AP). Individual and semi-structured interviews were subsequently carried out. The results revealed (a) the coexistence of absolute and relative pitch, (b) the students’ self-perception that the ear training, as well as the daily experience and practice, determine the degree of competence in performing the music activities, and (c) that the practice with the main musical instrument also modifies such competence in some particular music activities. In conclusion, these results suggest the elaboration of more far-reaching, specific aural training programs in music education centers.